A sintering method for dental glass ceramics
By selecting different sintering methods according to the scale rate of the glass ceramic body, the sintering deformation problem is solved and the edge adhesion of dental glass ceramics is ensured.
Patent Information
- Application Number
- CN202310068921.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-01-16
AI Technical Summary
Sintering method glass ceramic blanks are prone to deformation during the final firing process, affecting edge adhesion.
According to the different scale rate of glass ceramic body, different sintering methods are used: when the scale rate is greater than 1.15, a tooth mold with a strength greater than or equal to 8MPa is used to sinter it together; when the scale rate is less than or equal to 1.15, the restoration is placed on a highly polished zirconia ceramic sheet to sinter it, and the sintering temperature is controlled to not exceed 880℃.
It effectively prevents softening and deformation of glass ceramics and ensures that the edge adhesion after sintering meets the requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to dental glass ceramics, in particular to a sintering method for dental glass ceramics. Background Art
[0002] Oral restoration, commonly known as dental prosthesis, is mainly aimed at the treatment of tooth defects and missing teeth, such as inlays, full crowns, dentures, etc. It is an important branch of stomatology. Implant restoration, bonding restoration, and aesthetic restoration are the fastest-growing areas in modern oral restoration, which have significantly improved the treatment effect and level of oral restoration.
[0003] General tooth defects can be treated by filling. However, if the tooth defect is severe, the remaining tooth tissue is weak and cannot provide good retention for the filling, the remaining tooth itself and the filling cannot reach sufficient strength, or in order to achieve higher aesthetic requirements, filling treatment alone cannot achieve satisfactory results, then restorative treatment should be used.
[0004] The main treatment methods for repairing tooth defects include inlays, partial crowns, full crowns (metal crowns, metal-ceramic crowns, all-ceramic crowns), post and core crowns, etc.
[0005] After partial tooth loss, the treatment methods that can be used include removable partial dentures, fixed dentures (fixed bridges), overdentures, implant dentures, etc.
[0006] After all teeth are lost, the recommended treatment options for the mandible are, in order of priority, implant-supported overdentures, implant-supported fixed dentures, and conventional complete dentures. The recommended treatment options for the maxilla are: conventional complete dentures, implant-supported overdentures, and fixed dentures.
[0007] There are many types of denture-related products on the market, but most of them have problems of one kind or another. For example, CN109125801A discloses that there is no product or technology on the market that can acid-etch the surface of zirconia teeth after sintering and crystallization, whether chemical or physical, and processing the surface of zirconia has become a major problem. To this end, CN109125801A discloses a method for surface treatment of zirconium oxide in the field of dental restoration technology, and the specific steps of the method are as follows: processing a dental zirconium oxide block and grinding it into a zirconium oxide crown; then using a zirconium oxide dyeing solution to dye the crown, and drying the dyeing solution, and using a zirconium oxide crystallization furnace to sinter the zirconium oxide; immersing the zirconium oxide crown in a surface treatment solution to ensure that the inner and outer surfaces of the crown are in contact with the solution, the inner surface of the crown is used to bond to the abutment, and the outer surface is used for porcelain or glazing; taking the surface-treated zirconium oxide crown out of the solution and cleaning it, and porcelain or glazing the crown. The present invention improves the bonding strength between the abutment and the zirconia crown, and the bonding strength between the crown and the porcelain layer and the glaze layer by bonding the inner surface of the zirconia crown to the abutment and porcelain or glazing the outer surface after surface acid etching, thereby improving the aesthetics and durability of the dental restoration.
[0008] CN110104949A discloses a method for glazing a dental zirconia blank, and the main steps include: grinding of porcelain powder, screening and pulping, atomization test spraying, formal glazing, drying and coloring, high-temperature sintering, force detection, shaping and grinding, and secondary glazing. The method for glazing a dental zirconia blank described in the present invention ensures the quality of the glaze from the source by accurately controlling the ratio of porcelain powder to additives and the fineness of porcelain powder, and avoids cracking during the subsequent sintering process; at the same time, the glaze spraying method is used instead of the traditional glazing dipping method to make the glaze layer more consistent and avoid the interference of human experience; in addition, by implementing visual control in important sintering processes, problems that may occur during the firing process can be discovered in advance; by adding force detection after the firing is completed, the blank is tested by simulating the force condition of teeth when people chew, and the quality of the glaze layer is further guaranteed.
[0009] CN103058653A discloses a method for preparing a metal-stabilized zirconia composite ceramic for tooth restoration, which is prepared by a new template-sintering method. The preparation method is to process a metal template using micromachining technology, and then transfer the microstructure of the metal template surface to a polymer ultra-thin film; then coat nano-feldspar powder on the polymer ultra-thin film and sinter to obtain a feldspar porcelain with a micron through-hole structure; finally, fill the holes in the feldspar porcelain with metal-stabilized zirconia nano-powder and sinter to obtain a metal-stabilized zirconia composite ceramic. The composite ceramic prepared by the method of the present invention is composed of feldspar porcelain and metal-stabilized zirconia, and has a microstructure similar to that of tooth enamel: zirconia porcelain is used as glaze columns, and feldspar porcelain is used as column interstitial. This composite ceramic has excellent mechanical properties and toughness; it can be processed using CAD / CAM technology, and after processing, it is not necessary to decorate the surface with porcelain, thus avoiding the phenomenon of porcelain collapse, and can be used as a dental restoration material.
[0010] Lithium disilicate glass-ceramics have excellent mechanical properties and biocompatibility, as well as unique aesthetic properties, and are widely used in the field of dental restorations.
[0011] Lithium disilicate glass ceramics can be prepared by sintering, where the glass is melted, quenched, and ground into glass powder. The glass powder is formed and sintered to form a glass ceramic blank, which is processed into a restoration and then sintered. This sintering method for preparing glass ceramic blanks solves the problem of difficult glass ceramic processing and realizes dry milling of glass ceramics. However, this blank is in a semi-sintered state, and shrinkage and deformation will occur during the final firing process, which will affect the edge tightness of the final restoration.
[0012] Conventional casting glass ceramic glazing and sintering of zirconia restorations can be fixed with sintering paste. However, for sintered glass ceramic blanks, the penetration of sintering paste into the restoration will affect the transparency and color, and will also cause deformation and affect the edge tightness. Summary of the invention
[0013] The present invention aims to solve at least one of the above technical problems.
[0014] The invention provides a sintering method for dental glass ceramics, which can solve the deformation problem of glass ceramics sintered by sintering methods with different sizing ratios during the final sintering process, so that the edge tightness of the product after sintering meets the requirements.
[0015] A sintering method for dental glass ceramics, comprising:
[0016] 1) When the setting ratio of the glass-ceramic blank is greater than 1.15, the glass-ceramic blank is processed into a restoration; the restoration is placed on a dental cast and sintered together; wherein the strength of the dental cast is greater than or equal to 8 MPa, and the difference between the setting ratio of the dental cast and the setting ratio of the glass-ceramic blank is within ±0.003; or,
[0017] 2) When the glass ceramic blank has a draft ratio of less than or equal to 1.15, the glass ceramic blank is processed into a restoration; the restoration is sintered on a highly polished zirconia ceramic sheet, and the sintering temperature is controlled to be no greater than 880°C.
[0018] Optionally, the draft ratio of the glass-ceramic body in 1) is greater than 1.15 and less than or equal to 1.20; for example, 1.16, 1.17, 1.18, or 1.20.
[0019] Optionally, the glass ceramic body in 2) has a draft ratio of 1.10-1.15, such as 1.10, 1.12, 1.13, or 1.14.
[0020] Optionally, the surface roughness of the zirconia ceramic sheet in 2) is less than or equal to 0.02 μm, such as 0.01 μm, 0.02 μm or less.
[0021] Optionally, the final sintering temperature in the sintering temperature in 2) is not greater than 880°C.
[0022] Optionally, in 2), the final firing temperature is controlled at 800-880°C.
[0023] Optionally, in 2), the vacuum is released after the maximum temperature is reached, and the temperature is kept at least 1.5 minutes, such as 1.5-10 minutes.
[0024] Optionally, the total sintering time in 2) is no more than 40 min.
[0025] Optionally, the glass ceramic body is lithium disilicate glass ceramic.
[0026] Optionally, the restoration includes a crown, an inlay, or a veneer.
[0027] Optionally, the strength of the dental model is 8-30MPa.
[0028] Optionally, the difference between the scale ratio of the dental model and the scale ratio of the glass-ceramic body is -0.001, -0.002, -0.003, 0.001, 0.002 or 0.003.
[0029] Optionally, the dental mold is made by sintering zirconium oxide powder and feldspar powder.
[0030] Optionally, the proportion of zirconium oxide powder in the dental model is 20-45wt%. wt% is weight percentage.
[0031] Optionally, the zirconium oxide powder and the feldspar powder are mixed and pressed and then fired at 450-550° C. (eg, 500° C.) Optionally, the firing time is 1.5-2.5 hours, for example, 2 hours.
[0032] Optionally, the pressing pressure is 80-220 MPa, for example 100 MPa.
[0033] Optionally, the dental model matches the restoration.
[0034] In some examples, the method for preparing the dental mold includes: mixing and pressing zirconium oxide powder and feldspar powder, sintering at 450-550° C. for 1.5-2.5 hours, carving into a dental mold matching the restoration, and adjusting the pressure so that the scale ratio of the dental mold differs from that of the restoration by ±0.003.
[0035] In some instances, when the draft ratio of the glass-ceramic blank is greater than 1.15, the glass-ceramic blank is processed into a restoration; zirconium oxide powder and feldspar powder are mixed and pressed, and then sintered at 450-550° C. for 1.5-2.5 hours, and carved into a dental mold matching the restoration, and the pressure is adjusted so that the draft ratio of the dental mold differs from that of the restoration within ±0.003, and the strength of the dental mold is greater than 8MPa, and the restoration is placed on the dental mold and sintered together.
[0036] Optionally, the sintering in 1) and / or 2) is performed according to the following procedure:
[0037] 0-700℃: heating rate is 65-85℃ / min, vacuum degree is 500-5000Pa;
[0038] 700℃: keep warm for 1-6min, vacuum degree 500-5000Pa;
[0039] 700℃-Tmax: heating rate is 12-20℃ / min, vacuum degree is 500-5000Pa;
[0040] Tmax: The insulation time after vacuum is released is 1-10 minutes.
[0041] Wherein, the final firing temperature Tmax is between 850-880°C.
[0042] Optionally, the method further comprises the step of measuring the draft ratio of the glass ceramic blank. The step of measuring the draft ratio of the glass ceramic blank is performed before sintering.
[0043] Optionally, the glass ceramic blank can be milled into a restoration on a processing machine. The milling process on the processing machine to form a restoration is performed after measuring the glass ceramic blank's size ratio and before sintering.
[0044] Optionally, the processing machine is a 4-axis or 5-axis machine; wherein the processing method of the processing machine is dry milling.
[0045] In some implementations, the method includes:
[0046] Measure the setting rate of glass ceramic body;
[0047] Milling the glass ceramic blank on a processing machine to form a restoration;
[0048] If the setting ratio of the glass-ceramic blank is greater than 1.15, the glass-ceramic blank is processed into a restoration; the restoration is placed on a dental cast and sintered together; wherein the strength of the dental cast is greater than 8 MPa, and the difference between the setting ratio of the dental cast and the setting ratio of the glass-ceramic blank is within ±0.003; or
[0049] If the glass ceramic blank has a draft ratio less than or equal to 1.15, the glass ceramic blank is processed into a restoration; the restoration is sintered on a highly polished zirconia ceramic sheet, and the sintering temperature is controlled to be no greater than 880°C.
[0050] The present invention also includes dental glass ceramics prepared by the above method.
[0051] In the embodiment of the present invention, the scale ratio is equal to the cube of theoretical density / actual density.
[0052] Compared with the prior art, the present invention differentiates glass-ceramic blanks according to the size ratio, and provides sintered glass-ceramic blanks with different size ratios.
[0053] The invention solves the problem of sintering deformation, and in particular effectively prevents the problem of softening and deformation of glass ceramics.
[0054] The glass ceramics prepared by the technical solution of the present invention achieve good adhesion. DETAILED DESCRIPTION
[0055] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the art or the product instructions are used.
[0056] The sintering procedure and sintering system described in the present invention are the same. Tmax described in the present invention is the final sintering temperature. The release rate and release rate described in the present invention have the same meaning. The heat preservation time is 1.5 minutes, and vacuum release means that the heat preservation is carried out for 1.5 minutes under the vacuum release state.
[0057] The sintering temperature of 700°C is allowed to fluctuate within the range of 700°C±10°C, and all of these are within the protection scope of the present invention. The following glass ceramic blank is lithium disilicate glass ceramic.
[0058] Example 1-1
[0059] The glass ceramic blank with a ratio of 1.14 was dry milled in a 4-axis machining center. The processed crown (i.e., restoration) was sintered on a highly polished zirconia ceramic sheet with a surface roughness of 0.01 μm. The sintering was performed according to the following sintering schedule:
[0060] 0-700℃: Heating rate is 80℃ / min, vacuum degree is 3000Pa,
[0061] 700℃: keep warm for 1min, vacuum degree 3000Pa,
[0062] 700-875℃: Heating rate is 15℃ / min, vacuum degree is 3000Pa,
[0063] 875℃: Holding time 1.5min, vacuum release.
[0064] Comparative Example 1-1
[0065] The only difference from Example 1-1 is that the processed crown (ie, restoration) is sintered on a zirconia ceramic sheet with a surface roughness of 0.05 μm.
[0066] Comparative Example 1-2
[0067] The only difference from Example 1-1 is that the processed crown (ie, restoration) is placed on a common porous cordierite sintering plate for sintering.
[0068] Example 2-1
[0069] The glass ceramic blank with a relief ratio of 1.16 was dry milled in a 4-axis machining center to form a crown (i.e., restoration); 30wt% of zirconia powder and 70wt% of feldspar powder were mixed evenly, molded at 100MPa pressure, and sintered at 500℃ for 2h to form a dental mold matching the restoration. The dental mold had a relief ratio of 1.161 and a strength of 8MPa. The restoration was placed on the dental mold and sintered together. The sintering system was as follows:
[0070] 0-700℃: heating rate 80℃ / min, vacuum degree 3000Pa;
[0071] 700℃: keep warm for 1min, vacuum degree 3000Pa;
[0072] 700℃-875℃: heating rate 15℃ / min, vacuum degree 3000Pa;
[0073] 875℃: Holding time 1.5min, vacuum release.
[0074] Comparative Example 2-1
[0075] The glass ceramic blank with a relief ratio of 1.16 was dry milled in a 4-axis machining center to form a crown, which was then sintered on a zirconia sheet with a surface roughness of 0.02 μm. The sintering system was the same as that of Example 2-1.
[0076] Comparative Example 2-2
[0077] The glass ceramic blank with a relief ratio of 1.16 was dry milled in a 4-axis machining center to form a crown, which was then sintered on an ordinary porous cordierite sintering disk. The sintering system was the same as that in Example 2-1.
[0078] Example 3-1
[0079] The glass ceramic blank with a relief ratio of 1.17 was dry milled in a 5-axis machining center to form a crown; 25wt% of zirconia powder and 75wt% of feldspar powder were mixed evenly, molded at 80MPa pressure, and sintered at 500℃ for 2h to form a dental mold matching the restoration. The dental mold had a relief ratio of 1.172 and a strength of 8MPa. The restoration was placed on the dental mold, and the sintering system was as follows:
[0080] 0-700℃: heating rate 75℃ / min, vacuum degree 3000Pa;
[0081] 700℃: keep warm for 2min, vacuum degree 3000Pa;
[0082] 700-875℃: heating rate 20℃ / min, vacuum degree 3000Pa;
[0083] 875℃: Holding time 2.5min, vacuum release.
[0084] Comparative Example 3-1
[0085] A glass ceramic blank with a relief ratio of 1.17 was dry milled in a 5-axis machining center to form a crown, which was then sintered on an alumina sheet with a surface roughness of 0.05. The sintering system was the same as that in Example 3-1.
[0086] Comparative Example 3-2
[0087] The glass ceramic blank with a relief ratio of 1.17 was dry milled in a 5-axis machining center to form a crown, which was then sintered on an ordinary porous cordierite sintering disk. The sintering system was the same as that in Example 3-1.
[0088] Experimental example: tightness test
[0089] The fit test is to put the restoration on the dental model to see if it is loose or warped. The degree of warping and looseness is used to judge the fit. The test results are shown in the table below.
[0090]
[0091] The tightness test is also a test used to measure sintering deformation.
[0092] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for sintering dental glass ceramics, characterized in that: The method comprises: 1) When the setting ratio of the glass-ceramic blank is greater than 1.15 and less than or equal to 1.20, the glass-ceramic blank is processed into a restoration; the restoration is placed on a dental cast and sintered together; wherein the strength of the dental cast is greater than or equal to 8 MPa, and the difference between the setting ratio of the dental cast and the setting ratio of the glass-ceramic blank is within ±0.003; or, 2) When the glass ceramic blank has a draft ratio of 1.10-1.15, the glass ceramic blank is processed into a restoration; the restoration is sintered on a highly polished zirconia ceramic sheet, and the sintering temperature is controlled to be no greater than 880° C. The surface roughness of the zirconia ceramic sheet is less than or equal to 0.02 μm; The sintering described in 1) and / or 2) is carried out according to the following procedure: 0-700℃: heating rate is 65-85℃ / min, vacuum degree is 500-5000Pa; 700℃: keep warm for 1-6min, vacuum degree 500-5000Pa; 700℃-Tmax: heating rate is 12-20℃ / min, vacuum degree is 500-5000Pa; Tmax: 1-10min insulation time after vacuum release; Wherein, Tmax is the final firing temperature, and the final firing temperature Tmax is between 850-880°C.
2. The sintering method of dental glass ceramics according to claim 1, characterized in that: The glass ceramic body is lithium disilicate glass ceramic.
3. The sintering method of dental glass ceramics according to claim 1, characterized in that: The dental mold is formed by sintering zirconium oxide powder and feldspar powder.
4. The sintering method of dental glass ceramics according to claim 3, characterized in that: The proportion of zirconium oxide powder in the dental model is 20-45wt%.
5. The sintering method of dental glass ceramics according to any one of claims 1 to 4, characterized in that: The preparation method of the dental mold comprises: mixing and pressing zirconium oxide powder and feldspar powder, sintering at 450-550° C. for 1.5-2.5 hours, carving into a dental mold matching the restoration, and adjusting the pressure so that the scale ratio of the dental mold differs from that of the restoration by ±0.
003.
6. The sintering method of dental glass ceramics according to claim 5, characterized in that: When the draft ratio of the glass-ceramic blank is greater than 1.15, the glass-ceramic blank is processed into a restoration; the zirconium oxide powder and the feldspar powder are mixed and pressed, and then sintered at 450-550°C for 1.5-2.5h, and carved into a dental mold matching the restoration, and the pressure is adjusted so that the draft ratio of the dental mold and the draft ratio of the restoration differ within ±0.003, and the strength of the dental mold is greater than 8MPa, and the restoration is put on the dental mold and sintered together.
7. Dental glass ceramics prepared by the sintering method of dental glass ceramics according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of metal stable zirconia composite ceramics for dental restorations
CN103058653A
Zirconia surface processing method
CN109125801A
Method for glazing on dental zirconia billet
CN110104949A
Preparation method of zirconium oxide dental implant abutment
CN107162586A
Production method for ceramics dental restoration
JP2005034636A